Industrial training report: Hospital Canselor Tuanku Muhriz (HCTM) / Ahmad Hazim Kamaruddin - Kamaruddin, Ahmad Hazim (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report intended to give an overview of my internship experience at Hospital Canselor Tuanku Muhriz (HCTM), detailing the tasks, responsibilities, and knowledge gained throughout the program. The internship afforded practical exposure in the department called Unit Kesihatan Awam, which was invaluable for honing professional skills, enhancing problem-solving skills, and exposing interns to a healthcare environment. My relevant responsibilities include handling events and producing the report, which adds to my experience and knowledge. There is also an account of the challenges faced, solutions implemented, and recommendations for future interns. After all, this internship was an extremely enriching experience in that it connected academic knowledge with practical experience.